Gender representation in government-endorsed Arabic language textbooks: Insights from Indonesia - Kuraedah, St; Gunawan, Fahmi; Alam, Samsu; Ubaidillah, M. Faruq; Alimin, Alimin; Fitriyani, Fitriyani (Frontiers in Education, 2023)
Much research on textbook analysis has looked at diverse perspectives nested by the textbook authors, including gender equality. Although a growing body of research on gender representation in textbooks has been undertaken, there is a paucity of research on Arabic textbooks. This study aims to examine gender representation in Arabic textbooks for Islamic school students approved by the Ministry of Religion of Indonesia to fill the research gap. This research employed a case study design focusing on three textbooks. The researchers utilized thematic analysis anchored in Rifkin’s theory. The findings show that (1) gender representation in Arabic textbooks, verbally and visually, is dominated by men, (2) gender representation is visualized from six themes showing male dominance except for the theme “traveling,” which is dominated by women, and (3) the pedagogical actions that need to be taken to overcome these problems are (a) Arabic language teachers need to develop materials when using government-endorsed Arabic textbooks and (b) the Ministry of Religious Affairs should promote gender equality through recommended textbooks.